Gender Stereotypes toward Women: A Critical Discourse Analysis of Mata Najwa Talk Show “Susahnya Jadi Perempuan – Part 2” - I Gusti Ayu Mahatma Agung; Prisna Aswarita Putri (Universitas Muhammadiyah Semarang, 2023)
Gender stereotypes are views and beliefs about how men and women typically act in society. For example, women are supposed to be nurturing and feminine, while men are supposed to be strong and masculine. Gender stereotypes become problematic when they create certain expectations or limit opportunities for one social group. This study aims to examine gender stereotypes toward women in Mata Najwa Talk Show entitled “Susahnya Jadi Perempuan – Part 2”. This is a qualitative study that applies the theory of critical discourse analysis by Sara Mills. The theory focuses on the positioning of actors in the text, commonly known as the subject-object position and the writer-reader position. However, the subject-object position is the primary focus of this study. The results showed that the subjects are one woman and four men with various perspectives about gender stereotypes. According to the female subject, there are several negative stereotypes about women that are deeply ingrained in society. These stereotypes are caused by patriarchal values that prioritize men over women in terms of privilege, dominance, and power. The four male subjects have different views regarding the stereotypes about women. These various perspectives are due to different backgrounds, such as experience, education, family values, and social circle. Men who are raised in patriarchal families and are surrounded by people who have patriarchal values tend to adopt and internalize these values. Meanwhile, men who are aware of issues and obstacles faced by women are generally more understanding and considerate.